Factors That Cause Aggressive Behavior in Adolescents - Anatolij N. Arinin (Развитие образования, 2019)
This article is devoted to a theoretical analysis of the factors that cause aggressive behavior in adolescents. The relevance of the problem is out of question, since faced with the manifestations of aggression, teachers and psychologists experience difficulties in solving it, so there is an urgent need to identify the factors of aggressive behavior development in adolescents to find the best ways of its psychological and pedagogical correction. The purpose of the article is to consider the factors of aggressive behavior development in adolescents. During the study the following methods were applied: theoretical and analysis of home and abroad psychologists on the aggressive behavior in adolescents. In science, many points of view have been put forward about the causes of aggression, its nature and factors of development. However, with all the abundance of researches in modern Western and domestic psychology, there is a lack of elaboration of many aspects of the human aggression. There is no consensus on the definition of aggression and its cause, none of the theories can be perfect and accurate. The development of aggressive behavior in adolescents is a complex process that is multifactorial. Aggressive behavior of adolescents is formed due to the influence of family, peers, educational institutions, the media. It can be concluded that aggression as a phenomenon is actively manifested and present in the adolescent environment, both in a group and in individuals. And nowadays the scientific task is not only to study the factors of aggression and aggression itself as a phenomenon, but it also should be aimed at the shift of adolescents’ aggression to positive psycho-emotional activity to achieve personal positive results useful for society.